Suitability Evaluation of Land Use as Efforts to Improve Quality of Watershed - I Gede Budiarta (Media Komunikasi Geografi, 2016)
In general, this paper aims to determine the mechanism for setting land capability and function of the area in a watershed, and to determine the suitability of land use and land cover index in a watershed. The design of writing used is descriptive design with descriptive qualitative data analysis techniques. The results of the research literature review showed that 1) the classification of land capability class in a category is based on the intensity of the inhibiting factors. Land classified into eight classes that are marked with the Roman numerals I to VIII. Increased threat of damage or straight down barriers of class I to class VIII; 2) the type of function of the area was determined based on the value of land ability scores and other special criteria. Area function is determined based on the Minister of Agriculture No. 837 / Kpts / Um / 11/1980 and No. : 683 / Kpts / Um / 8/198; 3) the suitability of land use (KPL) in a river basin is determined based on a formula derived from the Regulation of the Minister of Forestry of the Republic of Indonesia Number: P. 32 / MENHUT-II / 2009; 4) The index of land cover to note because it is an important element in the mechanism of the watershed. The goal is to find a permanent vegetated land area in the watershed. Key words: land capability, land penggulahan, watersheds.